2021
DOI: 10.3390/molecules26216752
|View full text |Cite
|
Sign up to set email alerts
|

Attenuative Effects of Fluoxetine and Triticum aestivum against Aluminum-Induced Alzheimer’s Disease in Rats: The Possible Consequences on Hepatotoxicity and Nephrotoxicity

Abstract: Background: Alzheimer’s disease (AD) is a chronic neurological illness that causes considerable cognitive impairment. Hepatic and renal dysfunction may worsen AD by disrupting β-amyloid homeostasis at the periphery and by causing metabolic dysfunction. Wheatgrass (Triticum aestivum) has been shown to have antioxidant and anti-inflammatory properties. This work aims to study the effect of aluminum on neuronal cells, its consequences on the liver and kidneys, and the possible role of fluoxetine and wheatgrass ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Nuclear degeneration and pyknosis were found in the cerebral cortex, subiculum, and fascia dentata. These outcomes agree with earlier studies by Abu-Elfotuh et al and Hamdan et al [ 54 ]. The present study unveils the promising neuroprotective effects of cocoa-based nutraceuticals, either alone or in combination with other dietary supplements, in mitigating the underlying histopathological deterioration.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nuclear degeneration and pyknosis were found in the cerebral cortex, subiculum, and fascia dentata. These outcomes agree with earlier studies by Abu-Elfotuh et al and Hamdan et al [ 54 ]. The present study unveils the promising neuroprotective effects of cocoa-based nutraceuticals, either alone or in combination with other dietary supplements, in mitigating the underlying histopathological deterioration.…”
Section: Discussionsupporting
confidence: 94%
“…Like our results, cocoa exhibited anti-inflammatory activity by reducing inflammatory TNF-α in alcohol-induced liver toxicity models in rats [ 53 ]. In addition, it was reported previously that VIN and WG inhibited Aβ-induced toxicity by inhibiting TNF-α and IL-1β [ 54 ]. Prior research has revealed that EGCG can mitigate amyloid β-induced toxicity by modulating the activity of TNF-α [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…37 The pathophysiology of Alzheimer's disease is strongly linked to an uncontrolled neuroinflammatory process, like the overexpression of inflammatory mediators like IL-1β, which in turn suppresses the formation of the brain-derived neurotrophic factors responsible for the conduct of physiological functions in the CNS. 38,39 Furthermore, patients with high levels of AlCl 3 demonstrated cognitive deterioration, which has been linked to impaired pro-inflammatory regulators including TNF-α. 31 Cardiac glycosides like periplocin may be beneficial in addressing inflammation at the brain's periphery, opening up new avenues for medication development for neuroinflammatory degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental contamination with TTEs is both natural and anthropogenic. It can affect almost all the organs, but mainly the heart, kidney, liver, lungs, and nervous system [ 6 , 7 , 8 ].…”
Section: Toxic Trace Elements and Cardiotoxicitymentioning
confidence: 99%